Design of automatic control system based on unified timed hybrid Petri net (2017)
A practical problem in automation systems modeling is the choice between a fully hybrid approach and the fluidization of some parts conserving the general discrete event approach. This paper explores the approach based on specific hybrid parts into a discrete event system using a unified Petri nets environment called GHENeSys (General Hierarchical Enhanced Net System), which follows the ISO/IEC 15909 standard and includes extensions such as hierarchy and time concepts. Then, a design method based on GHENeSys Timed Hybrid Petri Net (GTHPN) technique is proposed to model these hybrid parts. GHENeSys subnets are associated with macro-places and help to control combinatorial explosion and has extended arcs to guarantee the GTHPN applicability to practical cases. All resulting models of the approach proposed could also benefit from an easier conversion to PLC programs in IEC 61131 representation. A case study is presented for producing constructive blocks showing the advantages of the current proposition.